Alexandria : the city that changed the world - Issa, Islam (Pegasus Books, 2024)
An award-winning British-Egyptian writer presents an authoritative history of the first modern city and how it has shaped our modern world, including its role as a global capital of knowledge as well as the site of plagues and violence. A city drawn in sand. Inspired by the tales of Homer and his own ambitions of empire, Alexander the Great sketched the idea of a city onto the sparsely populated Egyptian coastline. He did not live to see Alexandria built, but his vision of a sparkling metropolis that celebrated learning and diversity was swiftly realised and still stands today. Situated on the cusp of Africa, Europe and Asia, great civilizations met in Alexandria. Together, Greeks and Egyptians, Romans and Jews created a global knowledge capital of enormous influence: the inventive collaboration of its citizens shaped modern philosophy, science, religion and more. In pitched battles, later empires, from the Arabs and Ottomans to the French and British, laid claim to the city but its independent spirit endures. In this sweeping biography of the great city, Islam Issa takes us on a journey across millennia, rich in big ideas, brutal tragedies and distinctive characters, from Cleopatra to Napoleon. From its humble origins to dizzy heights and present-day strife, Alexandria tells the gripping story of a city that has shaped our modern world.